3D finite element modeling of pelvic organ prolapse. Issue 16 (9th December 2016) - Yang, Zhuo; Hayes, Jaclyn; Krishnamurty, Sundar; Grosse, Ian R.
Abstract: Objectives : The purpose of this study is to develop a validated 3D finite element model of the pelvic floor system which can offer insights into the mechanics of anterior vaginal wall prolapse and have the ability to assess biomedical device treatment methods. The finite element results should accurately mimic the clinical findings of prolapse due to intra-abdominal pressure (IAP) and soft tissues impairment conditions.Methods : A 3D model of pelvic system was created in Creo Parametric 2.0 based on MRI Images, which included uterus, cervix, vagina, cardinal ligaments, uterosacral ligaments, and a simplified levator plate and rectum. The geometrical model was imported into ANSYS Workbench 14.5. Mechanical properties of soft tissues were based on experimental data of tensile test results from current literature. Studies were conducted for IAP loadings on the vaginal wall and uterus, increasing from lowest to extreme values.Results : Anterior vaginal wall collapse occurred at an IAP value corresponding to maximal valsalva and showed similar collapsed shape as clinical findings. Prolapse conditions exhibited high sensitivity to vaginal wall stiffness, whereas healthy tissues was found to support the vagina against prolapse. Ligament impairment was found to have only a secondary effect on prolapse.